Desain Sistem Layanan dan Pencatatan Tagihan Perusahaan Daerah Air Minum (PDAM) Berbasis Web (Studi Kasus : Kecamatan Sukamerindu, Lahat) - Winardi, Pria; Bella, Monikha Oktra (SISKOMTI: Jurnal Sistem Informasi Komputer dan Teknologi Informasi, 2019)
The Regional Water Supply Company (PDAM) of Sukamerindu Subdistrict has customers covering 21 villages in Sukamerindu Subdistrict. With so many customers, the Regional Water Supply Company of Sukamerindu District must provide optimal services, especially services for recording PDAM water bills. The service system and the recording of water bill in the Regional Water Supply Company of Sukamerindu District will be built using PHP and MySQL and using the system development methodology, namely the Waterfall Model. The information system is connected directly to the internet network so that the service to the public in providing information on PDAM water bills quickly and precisely so as to make it easy for the public to find information about the water bill that must be paid by customers and help PDAMs to carry out these services.